Beğavî’nin Meâlimü’t-Tenzîl İsimli Tefsirinde Rivâyet Kullanımı (Secde Sûresi Örneği) - Erkaya, Musa; Beyaz, Mustafa (Fırat University, 2024)
İslâm dininin iki temel kaynağından biri olan sünnet, nakil yolu ile günümüze kadar ulaşmıştır. Kur’ân’ın ilk müfessiri olan Allah Rasûlü, ayetlerdeki kapalılıkları, nüzul sebebini ve bağlamını açıklamıştır. Zira onun tebliğ görevinin yanında, tebyîn görevi de bulunmaktadır. İşte bu sebeple sünnet de tıpkı Kur’ân gibi temel kaynak sayılmıştır. Kur’ân on dört asır önce tedrîcî olarak yirmi üç yılda nâzil olmuş, Hz. Peygamber’in yaşantısı ile hayata geçmiştir. O’nun ahirete irtihali ile birlikte ise Müslümanlar Kur’ân ve sünneti doğru anlayıp hayatlarına hâkim kılma çabası içerisine girmişlerdir. Bunun için büyük rihleler yapıp çeşitli eserler meydana getirmişlerdir. Bu eserlerin başında da tefsirler gelmektedir. Kur’ân ayetlerinin Hz. Peygamber, sahabe ve tâbiûn sözleriyle açıklandığı tefsirlere rivayet tefsirleri denmektedir. İşte Meâlimü’t-tenzîl de Beğavî (öl. 516/1122) tarafından bu metotla yazılan önemli bir tefsirdir. Büyük Selçukluların kuruluş ve yükseliş döneminde yaşamış olan Beğavî, Horasan bölgesinde Merverrûz ile Herat şehirleri arasındaki küçük bir kasaba olan Bağşur veya Bağ’da 433/1041 yılında doğmuştur. Buraya nisbetle de kendisine Beğavî denilmiştir. O, 516/1122 yılında Merverrûz’da vefat etmiştir. Çok iyi bir eğitim almış ve tefsir, hadis, fıkıh ve kıraat ilimlerinde eser vermiştir. Müellif, sekseni aşkın hocadan İslam âleminde Kütüb-i Sitte olarak tanınan eserler başta olmak üzere birçok hadis kitabını okumuştur. Ebû Ömer Abdülvâhid el-Melîhî’den (öl. 463/1071) Buhârî’nin el-Câmiu’s-sahîh’ini, Ebû Tâhir Ömer b. Abdilazîz’den (öl. 463/1071) Ebû Dâvud’un Sünen’ini, Ebu’l-Hasen Muhammed b. Muhammed ibn Saîd eş-Şîrezî’den (öl. ?) Mâlik b. Enes’in Muvatta’ını rivayet etmiştir. Öyle ki Meâlimü’t-tenzîl’in yanısıra Şerhu’s-sünne adlı eserinde naklettiği isnatlı rivayetlerin önemli bir kısmının adı geçen hocalarından dinlediği rivayetler olduğu görülmektedir. Beğavî’nin isnad bilgisi de üst düzeyde olup, naklettiği hadislerin senetlerini ve bu senetlerde yer alan râvilerin durumlarını çok iyi bilmektedir. O, rivâyet ettiği hadislerin senet tenkidini yapmasının yanı sıra sıhhat değerlendirmesinde bulunmuş ve bu konuda da kendisinin bir otorite olduğunu göstermiştir. Meâlimü’t-tenzîl, Beğavî’nin en tanınmış eseridir. Sözü edilen kitapta âyetleri merfu, mevkuf, maktu hadisler ile sonraki âlimlerden menkul âsâr ile açıklamaktadır. O’nun hadisçi kimliği ağır bastığından kendinden önceki tefsirlerde yer alan za¬yıf ve uydurma rivâyetleri tenkit etmiş¬tir. Ayetlerin tef¬sirinden önce sûre adını, âyet sayısını, Mekkî mi? Medenî mi? olduğunu ve hangi olay hakkında nazil olduğunu belirtmiştir. Âyetleri önce dilsel açıdan değerlendirmiş, sonra di¬ğer âyet ve hadislerle açıklamış, sahâbe ve tabiûn görüşlerinden istifade etmiştir. Ayrıca geniş bir şekilde kıraat vecihlerini izah etmiş, şâz kıraatleri zikretmiş, sarf ve nahiv tahlilleri yapmıştır. Âyetlerin tefsiri esnasında müellifin hadis alanındaki otori¬tesi açıkça görülmektedir. Eserde İsrâilî haberlere de yer vermekle birlikte, zaman zaman bunları tenkit süzgecinden ge¬çirerek bazılarını reddetmiştir. Makalede Secde Sûresinin tefsirinde müellifin rivayet kullanım yöntemi ve bu rivayetlerin sıhhat değerinin tespiti amaçlanmıştır. Bu bağlamda ilk önce Beğavî’nin hayatı ve tefsiri tanıtılmıştır. Daha sonra ise müellifin sûrenin tefsirini yaparken naklettiği 16 rivâyetin tahrîç ve sıhhat değerlendirmesi yapılmıştır. Rivâyetler başta müellifin hadis eserleri Şerhu’s-sünne ile Mesâbîhu’s-sünne’de akabinde ise diğer muteber hadis kitaplarında araştırılmıştır. Münekkid muhaddis ve muhakkiklerin kanaatlerinden yola çıkarak rivâyetlerin sıhhat değerleri ortaya konmuştur. Tespitlerimize göre 16 rivayetin 12’si isnatlı, 4’ü ise isnatsız olarak nakledilmiştir. Rivâyetlerin 12’sine Şerhu’s-sünne’sinde 9’una ise Mesâbîh’inde yer vermiştir. Geri kalan 4 rivâyet ise her iki eserinde de yer almamaktadır. Rivâyetlerin, içerisinde yer aldığı temel hadis kaynakları bakımından dağılımı ise şöyledir. 16 rivâyetten 15'i Kütüb-i Tis’a’da bulunmaktadır. Mezkûr rivayetlerden 5'ini Buhârî, 7’sini Müslim, 4’ünü Ebû Dâvûd, 6’sını Tirmizî, 2’sini Nesâî, 2'sini İbn Mâce, 1’ini Dârimî, 1'ini Mâlik b. Enes, 10'unu ise Ahmed b. Hanbel eserlerinde tahric etmişlerdir. Senedinin müntehâsı bakımından 1'i kudsî, 15'i ise merfû’dur. Sıhhat bakımından ise, 16 rivâyetin 3’ü müttefekun aleyh olmak üzere 10'u sahîh, 2’si hasen, 4’ü ise zayıftır.

Sunnah, one of the two basic sources of the Islamic religion, has survived to the present day through transmission. The Messenger of Allah, the first interpreter of the Quran, explained the obscurities in the verses, the reason for their revelation and their context. Because, in addition to his duty to convey, he also has a duty to inform. For this reason, the Sunnah is considered a basic source, just like the Qur’an. The Qur’an was revealed fourteen centuries ago, gradually over twenty-three years. It came to life with the life of the Prophet. After his passing into the afterlife, Muslims began to strive to understand the Qur’an and Sunnah correctly and to make them dominate their lives. For this reason, they made great scientific journeys and produced various works. At the beginning of these works are commentaries. Commentaries in which the verses of the Qur’an are explained with the words of the Prophet, his companions, and the followers are called narration tafsir. Maâlim at-tanzîl is an important commentary written by Baghawi (d. 516/1122) using this method. Baghawi, who lived during the founding and rise of the Great Seljuks, was born in 433/1041 in a small town called Bagshur or Bag, located between Marwarruz and Harat in the Khorasan region. In reference to this place, he was called Baghawi. He died in Marwarruz in 516/1122. He received a very good education and trained himself to produce works in the sciences of tafsir, hadith, fiqh and recitation. He narrated the Bukhari's al-Jâmi al-Sahîh from Abu Omar Abdulwahid el-Melihi (d. 463/1071), Abu Dawud’s Sunan from Abu Tahir Omar b. Abdelaziz ibn Ahmed al-Marwazi al-Fashani (d. 463/1071), Malik b. Anas’s Muwatta’ from Abu’l-Hasan Muhammed b. Muhammed ibn Saîd al-Shrazi (d. ?). So much so that it can be seen that a significant part of the attributed narrations he narrated in his work called Sharhu's-sunna, as well as Maâlim at-tanzil, were the narrations he heard from the mentioned teachers. Baghawi's knowledge of isnad is also at a high level and he knows very well the narrations of the hadiths he narrated and the situations of the narrators in these narrations. In addition to criticizing the hadiths he narrated, he also evaluated their authenticity and showed that he was an authority on this subject. Maâlim at-tanzil is Baghawi's most well-known work and explains the verses with hadiths, the views of the companions, followers and later scholars. Since he was also a good haddith, he criticized the weak and fabricated narrations in the previously written commentaries. In Maâlim at-tanzil, before starting the commentary, the name of the sura, the number of verses, whether it is Meccan or Medinan, where and about what event it was revealed, are stated. First, explanations were made on the verses in terms of dictionary. Then, the interpretation of the verse with other verses and hadiths was started, the views of the companions and the followers were used, the explanation of the recitation aspects was given in detail, the different recitations were mentioned, the grammatical and syntax analyzes were made. The authority of the author in the field of hadith is clearly seen in the interpretation of the verses. The main feature of the work is that it is frequently referred to hadiths, unlike Masâbihu’s-Sunnah, most of the hadiths are narrated with their sources and almost all of them are based on the author himself. Although Israeli news were included in Maâlim at-tanzil, the author sometimes criticized them and rejected some of them. The aim of the article is to determine the author's method of using narrations in the interpretation of Surah al-Sajdah and the authenticity of these narrations. In this context, first Baghawi’s life and commentary are introduced. Later, the extraction and authenticity of the 16 narrations that the author conveyed while interpreting the surah were evaluated. The narrations have been researched in al-Kutub al-Tis'a and other reliable hadith books, especially Sharhu's-sunnah and Masâbihu's-sunnah. Based on the opinions of critics and scholars, the authenticity values of the narrations have been revealed. According to our findings, 12 of the 16 narrations were narrated with isnad and 4 without isnad. While 12 of the narrations are located only in Sharhu's-sunnah, 9 of them are only included in Masâbihu's-sunnah. The remaining 4 narrations are not included in either of his works. The distribution of the narrations in terms of the main hadith sources they are included in is as follows: 15 out of 16 narrations are located in al-Kutub al-Tis'a. 5 of these are in Bukhari, 7 in Muslim, 4 in Abu Dawud, 6 in Tirmidhi, 2 in Nasai, 2 in Ibn Majah, 1 in Darimi and 1 in Malik b. Anas’s Muwatta’ and 10 of them in Ahmed b. Hanbel. In terms of the end of the isnad, 1 is kudsî and 15 is marfû‘. In terms of authenticity, out of 16 narrations, 10 are sahih, 3 of which are muttefakun aleyh, 2 are hasan and 4 are weak.
The Use of Narration in Baghawi Commentary Named Maâlim at-Tanzîl (Example of Surah al-Sajdah)
Keywords: Hadith; Hadis